2000
DOI: 10.1086/312441
|View full text |Cite
|
Sign up to set email alerts
|

η Carinae: Binarity Confirmed

Abstract: We report the recovery of a spectroscopic event in h Carinae in 1997/1998 after a prediction by Damineli in 1996. A true periodicity with days (0.2% uncertainty) is obtained. The line intensities and the P = 2020 ‫ע‬ 5 radial velocity curve display a phase-locked behavior, implying that the energy and dynamics of the event repeat from cycle to cycle. This rules out S Doradus oscillation or multiple shell ejection by an unstable star as the explanation of the spectroscopic events. A colliding-wind binary scenar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
193
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(206 citation statements)
references
References 10 publications
13
193
0
Order By: Relevance
“…Optical spectroscopic observations unveiled a peculiar cyclic behaviour, showing regularly repeating excitation minima with a period of 5.53 years (Damineli et al 2000). A similar behaviour was also found at other wavelength bands, from radio to X-rays, which is commonly interpreted in terms of a highly eccentric binary model composed of an S Dor-type very luminous primary star, and an unseen early type secondary star.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Optical spectroscopic observations unveiled a peculiar cyclic behaviour, showing regularly repeating excitation minima with a period of 5.53 years (Damineli et al 2000). A similar behaviour was also found at other wavelength bands, from radio to X-rays, which is commonly interpreted in terms of a highly eccentric binary model composed of an S Dor-type very luminous primary star, and an unseen early type secondary star.…”
Section: Introductionsupporting
confidence: 67%
“…The LECS image will not be discussed here, as this paper is devoted to the analysis of the compact hard component which dominates beyond ∼2 keV. The observation date corresponds to phase 1.457 of the spectral variation cycle of 5.53 yr (Damineli et al 2000), assuming Φ = 1 for the 1998.0 minimum. Figure 1 shows the MECS images of the region around η Car using photon events selected from three different energy bands, in order to trace the softer and harder X-ray sources in the field and to map the regions emitting in the 6.7 keV iron line.…”
Section: Observationsmentioning
confidence: 99%
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%
“…For instance, radio (Duncan et al 1995), millimetre (mm, Abraham et al 2005), optical (Damineli 1996;Damineli et al 2000), near-infrared (near-IR, Whitelock et al 1994Whitelock et al , 2004Damineli 1996), and X-ray (Corcoran 2005) observations, obtained over the past few decades, have unveiled the existence of a period of ∼2022.7 ± 1.3 days (Damineli et al 2008).…”
Section: Introductionmentioning
confidence: 99%